Pelaksanaan Pendidikan Karakter Bagi Anak Jalanan (Studi Kasus di Rumah Singgah dan Belajar Diponegoro) - Turah Asih Lestari (Universitas Negeri Makassar, 2017)
The purpose of this study is to know the implementation of character education for street children, and the efforts of the board to instill character education for street children in the shelter and learn Diponegoro, and to describe and analyze the character education for street children. This research is a qualitative research by taking the background Shelter and Learning Diponegoro Depok Sleman Yogyakarta. Data collection is done by conducting observation, interview and documentation. The results showed that: (1) the implementation of character education done anywhere and anytime without any written plan about the character to be implanted. From the process there are several values of character that are planted among them are religious, responsibility, discipline, independence, honesty. (2) Efforts made by the board or mentor in inculcating the character is through the guidance of learning that is held once a week for street children home visit while for street children in the house caretaker or companion to provide daily schedule from waking up to sleep again.